2021
DOI: 10.37766/inplasy2021.5.0097
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Vertebral Augmentation for Osteoporotic Vertebral Compression Fractures Will Increase the Number of Subsequent Fractures at Adjacent Vertebral Levels: A Systematic Review and Meta-analysis

Abstract: Review question / Objective: This study aimed to investigate whether percutaneous v e r t e b r a l a u g m e n t a t i o n ( P VA ) w a s associated with clinical and radiological subsequent adjacent fractures in patients with osteoporotic vertebral compression fractures. Condition being studied: Osteoporotic vertebral compression fractures (OVCFs) are common complications of osteoporosis and often result in back pain, spinal deformity, functional disability, and even death. Hence, they have become one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…DPQ included four aspects of daily activity (da), work and entertainment (wl), anxiety and depression (ad), and social interest (SI). A higher score indicated more severe pain ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPQ included four aspects of daily activity (da), work and entertainment (wl), anxiety and depression (ad), and social interest (SI). A higher score indicated more severe pain ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…DPQ included four aspects of daily activity (da), work and entertainment (wl), anxiety and depression (ad), and social interest (SI). A higher score indicated more severe pain (12). ( 4) The MOS short-term (SF-36) scores of the health survey before treatment, 3 days after treatment, 3 months after treatment, and 6 months after treatment were compared between the two groups.…”
Section: Data Collection and Clinical Evaluationmentioning
confidence: 99%
“…However, the frequency of vertebral refracture after PVP is equal to that without PVP. Vertebral refractures after PVP can also occur in adjacent as well as distant vertebral bodies [ 3 , 24 , 48 , 49 , 69 ], but, empirically, patients who are re-treated for recurrence of compression fractures a few days after PVP have often new compression fractures of adjacent vertebral bodies directly above or below the PVP-treated vertebral body [ 96 ]. Prophylactic PVP as an optional treatment is preferably performed on normal upper and lower vertebral bodies adjacent PVP-treated vertebra [ 97 , 98 ].…”
Section: Potential Risk Of Pvp Procedures For Osteoporotic Vertebral ...mentioning
confidence: 99%
“…Nowadays, PVP and percutaneous kyphoplasty (PKP), with safety and efficacy, are widely used in the treatment of patients with OVCF ( 5 7 ). However, some studies reported that adverse events such as cement leakage, pulmonary cement embolism, and new vertebral compression fracture (VCF) occurred after PVP or PKP ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%